Pengaruh Kualitas Layanan, Citra Perusahaan, dan Word Of Mouth Terhadap Kepuasan Konsumen Pada Klinik Mata Tritya Surabaya. - Muhammad Dandy Arif Fath Syabana; Estik Hari Prastiwi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze and prove the influence of service quality, corporate image, and word of mouth partially and simultaneously on customer satisfaction at Tritya Eye Clinic Surabaya. This study involved 96 respondents selected using purposive sampling technique. The data to be collected is in the form of a questionnaire and data analysis using multiple linear regression analysis method which is then continued with t-test for separate testing, F-test for simultaneous testing of the dependent variable, coefficient of determination to measure the strength between the independent and dependent variables. Based on the results of the validity and reliability tests, the indicators that have been tested are proven to be valid and consistent. The results of the t-test indicate that the three variables have a significant influence on customer satisfaction, while the f-test explains that the three variables simultaneously have a significant influence. Thus, the conclusion is that service quality, corporate image and word of mouth have an influence on customer satisfaction.